2016
DOI: 10.1155/2016/6792731
|View full text |Cite
|
Sign up to set email alerts
|

Micro Fine Sized Palm Oil Fuel Ash Produced Using a Wind Tunnel Production System

Abstract: Micro fine sized palm oil fuel ash (POFA) is a new supplementary cementitious material that can increase the strength, durability, and workability of concrete. However, production of this material incurs high cost and is not practical for the construction industry. This paper investigates a simple methodology of producing micro fine sized POFA by means of a laboratory scale wind tunnel system. The raw POFA obtained from an oil palm factory is first calcined to remove carbon residue and then grinded in Los Ange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The raw POFA used in this research is collected from a local palm oil mill (Bau, Lundu Palm Oil Mill, Sarawak, Malaysia) and is treated before grinded to produce particle sizes ranging from 1-10 μm [5,6].…”
Section: Methodsmentioning
confidence: 99%
“…The raw POFA used in this research is collected from a local palm oil mill (Bau, Lundu Palm Oil Mill, Sarawak, Malaysia) and is treated before grinded to produce particle sizes ranging from 1-10 μm [5,6].…”
Section: Methodsmentioning
confidence: 99%
“…Reportedly, the replacement of POFA by weight of the binder with volume exceeding 15% reduced the concrete strength, except for the substitution volume limited to 10% or less with an average density [ 25 , 60 , 79 ]. The absolute density of unground POFA is almost 60% lesser than that of OPC due to the porosity of the POFA particle [ 23 , 43 , 60 , 69 ]. Ranjbar et al [ 51 , 64 ] reported that the bulk densities of self-compacting concrete (SCCs) comprising 20%, 15%, and 10% POFA condensed by 5.75%, 4.96%, and 3.68%, correspondingly, in comparison with the reference samples.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Quite a few studies found a little segregation in all concrete mixes contained numerous POFA contents [ 14 , 37 , 39 , 43 , 47 , 75 , 92 , 117 ]. The research reported that concrete mixture with 10% and 15% POFA were highly stable and had a visual-stability-index (VSI) results of “0” and “1”, indicating that a lack of sign of segregation except quite a minor bleeding, respectively [ 92 , 94 ].…”
Section: Fresh Propertiesmentioning
confidence: 99%
“…These by-products are used as fuel to heat up boiler for generation of electricity in the palm oil mill. As the second largest palm oil producer in the world, Malaysia has generated million tonnes of palm oil wastes each year [1,3,12]. The extracted product from the boiling process is known as palm oil fuel ash (POFA) which comprises a large amount of silica, thus, possesses pozzolanic properties suitable as cement replacement material.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies are able to produce micro fine sized POFA, the cost of production is still too expensive and the methods used are considered not effective [3,13]. Due to the significance contribution of micro fine sized POFA as a new potential cement replacement material, an effective and economical method to produce micro…”
Section: Introductionmentioning
confidence: 99%